Healthcare needs of adolescents with congenital heart disease transitioning into adulthood: a Delphi survey of patients, parents, and healthcare providers. (February 2017) - Chen, Chi-Wen; Su, Wen-Jen; Chiang, Yueh-Tao; Shu, Ying-Mei; Moons, Philip
Background: The increasing survival of children with congenital heart disease (CHD) challenges healthcare systems regarding how to manage the many health needs of patients undergoing transitional care. A comprehensive understanding of the perspectives of patients, parents, and healthcare providers is required. Objective: This study systematically identified the healthcare needs of adolescents with CHD transitioning into young adults by collecting the perspectives of patients, parents, and healthcare providers. Methods: A sample of CHD patients ( n = 29), parents of children with CHD ( n = 29), and healthcare providers ( n = 16) completed the two-round Delphi study, and 64 healthcare needs were identified. The central tendency and the level of dispersion were computed in order to establish a consensus. Results: A consensus was reached on 25 healthcare needs including health, family, individual, interpersonal interaction, and policy dimensions, which were classified as important with a moderate to high level of agreement by all three groups. The three groups were strongly agreed that "encouraging the patient to learn health self-management" and "cultivating a positive attitude toward the illness" were very important. The opinions of the three groups differed significantly on 12 needs ( p < 0.05) related to health, family, and policy dimensions. Conclusion: A consensus was reached on the needs that were identified as being potentially valid measures of the healthcare needs of adolescents with CHD transitioning into young adults. The identified needs can serve as the basis for establishing a transitional health passport and developing a clinical intervention for adolescents with CHD transitioning into young adults.